2007
DOI: 10.1177/154193120705101844
|View full text |Cite
|
Sign up to set email alerts
|

Assessing temporal support for dynamic decision making in C2

Abstract: Temporal awareness is key to successful decision making in a wide range of command and control situations, yet little explicit support to maintaining temporal awareness is provided by Decision Support Systems (DSS) for time-critical decisions. In the context of simulated weapon-target scheduling, the present study compared the decision support gained from two display formats: typical geospatial display and temporal display. The results demonstrated that the temporal display facilitates scheduling performance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Modifications to the TOD interface would make the temporal information it provides more salient and easier to extract. This may have been particularly the case for novice users, as a previous study found that participants were able to use TOD to better advantage only when they had more experience (Rousseau et al, 2007). NSEEV also highlights the effort required to shift attention across the screen.…”
Section: Methodological and Practical Implicationsmentioning
confidence: 93%
See 2 more Smart Citations
“…Modifications to the TOD interface would make the temporal information it provides more salient and easier to extract. This may have been particularly the case for novice users, as a previous study found that participants were able to use TOD to better advantage only when they had more experience (Rousseau et al, 2007). NSEEV also highlights the effort required to shift attention across the screen.…”
Section: Methodological and Practical Implicationsmentioning
confidence: 93%
“…We suggest that the mere presence of a support tool on the screen can alter the way a task is performed and can add additional load (McCrickard, Catrambone, Chewar, & Stasko, 2003;Rousseau et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it is a challenge to portray temporal information outside of the geospatial context, with no reference to space. For example, Rousseau, Tremblay, Lafond, Vachon, and Breton (2007), in the context of simulated naval weapon-target scheduling, showed that a temporal display promoted the use of appropriate time-based heuristics but only after substantial practice. It can indeed be challenging to consider all other situational dimensions when visualizing time-oriented data.…”
Section: Decision Support Interfacesmentioning
confidence: 99%
“…The Simulated Combat Control System (S-CCS) microworld (Rousseau, Tremblay, Lafond, Vachon, & Breton, 2007) is a SME-validated, low-level, computer-controlled simulation of single ship naval anti-air warfare that requires no particular expertise. The simulation is dynamic and the evolution of associated scenarios is determined by the actions of the operator.…”
Section: Microworldmentioning
confidence: 99%